Caracterización de la depresión en cinco madres gestantes, habitantes del municipio de Corinto-Cauca (2023)
Pregnancy is a state in which a woman goes through various changes in her physical, hormonal, psychological and social condition; These may present other variations and alterations to mental health, if the presence of a depressive disorder is detected during the gestation period, which is one of the most common reasons for consultation in the psychological field. Learning to be a mother, her physical transformations, the different perceptions of her sociocultural context act as protective or risk factors, which makes it important to conduct inquiries regarding her emotional state.